1997
DOI: 10.1557/proc-476-147
|View full text |Cite
|
Sign up to set email alerts
|

Metalized Polypropylene Film in Capacitors: Characterization and The Effect of Interfacial Pressure on the Dielectric Strength

Abstract: Metalized polypropylene film used in high energy density capacitors has been mechanically characterized to determine its elastic constants. The out of plane coefficient of thermal expansion (CTE) of the orthotropic film is 10 times as large as the smaller in plane CTE. The out of plane modulus is twice as large compared to one of the in plane moduli. The effect of interfacial pressure on the dielectric breakdown is also studied for the same film. It is observed that the dielectric strength of the film decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Studies on MPFC lifetime and its influencing factors mainly focus on failure mechanisms, reliability evaluations, and MPFC lifetime predictions under temperature, voltage, and humidity conditions [9][10][11][12][13]. The explorations of mechanical stress performed in MPFCs were mainly concentrated on internal pressure distribution [14], the calculation of internal pressure [15], and breakdown characteristics [16,17]. According to the literature [18], the research results revealed that interlayer pressure has a negative effect on the breakdown characteristics of the studied materials.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on MPFC lifetime and its influencing factors mainly focus on failure mechanisms, reliability evaluations, and MPFC lifetime predictions under temperature, voltage, and humidity conditions [9][10][11][12][13]. The explorations of mechanical stress performed in MPFCs were mainly concentrated on internal pressure distribution [14], the calculation of internal pressure [15], and breakdown characteristics [16,17]. According to the literature [18], the research results revealed that interlayer pressure has a negative effect on the breakdown characteristics of the studied materials.…”
Section: Introductionmentioning
confidence: 99%